Kelimpahan Jenis Burung di Areal Kampus Universitas Tadulako dan Pemanfaatannya sebagai Media Pembelajaran - Musdayanti Musdayanti; Fatmah Dhafir; Syech Zainal (Universitas Tadulako, 2022)
This study aims to describe the abundance of bird species in campus area of the Tadulako University and the results of this study is used as a Pocket Book about bird species as a medium for learning biology. The method used is the IPA (Indices Ponctual Abundance) method with a purposive sampling technique. The results of this study found 25 species of birds including: Lanius sahach, Passer montanus, Pycnonotus aurigaster, Lalage sueurii, Hirundo rustica, Saxicola caprata, Lonchura pallida, Corvus enca, Gerygone sulphurea, Acridotheres javanicus, Hirundo rustica, Saxicola caprata, Lonchura pallida, Corvus enca, Gerygone sulphurea, Acridotheres javanicus, Necterinia jugulopus, Stylus , Ptilinopus melanospilus, Streptopelia chinensis, Geopelia striata, Centropus bengaleansis, Cacomantis merulinus, Merops philippinus, Todirhampus chloris, Collocalia esculenta, Turnix suscitatur, Gallirallus torquatus, Falco moluccensis, Cystola moluncensis, Cisticola juncid. 8 orders, 21 families, and 25 genera. and for the dominant abundance level there are 5 types namely Passer montanus, Pycnonotus aurigaster, Hirundo rustica, Lonchura pallida, and Zosterops palpebrosus. Evaluation of media by content experts by 78%, design experts by 84%, and media experts by 67.14%. Validation from students as many as 15 people amounted to 87.25% thus the pocket book media was declared fit for use as a learning medium.